Clinical accuracy of post graduate student in diagnosing congenital heart diseases (CHD) using an algorithmic approach and its comparison with echocardiography - Dr. Nirbhay Mehta; Dr. Swati Bhalse (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: Congenital heart diseases (CHDs)are an important cause of morbidity and mortality in children. In view of poor availability of resources in developing nations like India, clinical evaluation of children with CHD is important.Aim: To study the clinical accuracy of post graduate student in diagnosing congenital heart diseases and its comparison with echocardiography.Subjects and Methods: A prospective cross-sectional study performed in the Department of Pediatrics of a tertiary level teaching hospital in central India. Participants were children with CHDs attending outpatient department or admitted in wards or PICU. History, general physical and cardiovascular examinations were recorded by the post graduate student. Chest X-ray and ECG were obtained. These findings were used to classify the defect using an algorithm and a clinical diagnosis was made which was matched with echocardiography. Kappa coefficient test was used to judge the degree of agreement between the two methods.Results: 80 patients with CHDs were included in the final analysis. 49 (61.25%) had acyanotic CHDs and ventricular septal defect (VSD) was the most common defect (n= 24, 30%) while tetralogy of Fallot (TOF) was the most common (n=14, 17.5%) cyanotic CHD. Concordance of clinical diagnosis and echocardiography was maximum for VSD (16/24, 66.6%) in acyanotic group and TOF (8/14, 57%) in cyanotic group. Kappa’s coefficient test analysis also showed an "almost perfect" area of agreement for VSD (κ=0.87) and fair area of agreement for TOF (κ=0.65). For type of CHD (cyanotic or acyanotic) and type of ventricular hypertrophy (left, right or biventricular) it showed “almost perfect” and“fair” area of agreement respectively. Conclusion: Agreement between echocardiography and cclinical diagnosis of CHDs including hemodynamic parameters like type of ventricular hypertrophy and pulmonary arterial hypertension was reasonably accurate in our study.